Bi-component conductive silver paste and use method and application thereof
By using epoxy resin containing benzene ring structure and aliphatic epoxy resin with double epoxy functional groups, combining aromatic amines and acid anhydride curing agents, the crosslinking reaction is facilitated, and the existing room temperature curing two-component conductive silver paste cross-linking is solved. The problem of insufficient coupling degree has achieved two-component conductive silver paste with high shear strength and good conductivity.
Patent Information
- Application Number
- CN202411718129.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-07
AI Technical Summary
The crosslinking degree of existing room temperature cured two-component conductive silver paste is limited, resulting in low shear strength and poor conductivity after curing.
Using long-chain epoxy resin A containing at least two benzene ring rigid structures and aliphatic epoxy resin B containing double epoxy functional groups, combining aromatic amine-based curing agents and acid anhydride-based curing agents to promote cross-linking reactions and form high cross-crossing. Network structure of connection density.
The shear strength and conductivity of the two-component conductive silver paste are significantly improved, with shear strength up to 13.96MPa and resistance as low as 21Ω.
Smart Images

Figure BDA0005157496750000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive silver paste, and in particular to a two-component conductive silver paste and a use method and application thereof. Background Art
[0002] Two-component conductive silver paste is widely used in electronic components and circuits, especially in the photovoltaic field. Traditional two-component conductive silver paste is mostly cured at high temperature. High temperature will accelerate the curing process of the resin. As the temperature rises, the movement between the resin molecules intensifies, allowing the resin to form a cross-linked structure faster; however, high-temperature curing is costly and the process is complicated. Therefore, a two-component conductive silver paste that can be cured at room temperature has been developed. However, the current room-temperature curing two-component conductive silver paste has a limited degree of cross-linking at room temperature. The shear strength of the cured two-component conductive silver paste is generally 6MPa, and the resistance value is generally 1×10 6 Ω, low shear strength and poor conductivity. Summary of the invention
[0003] The object of the present invention is to provide a two-component conductive silver paste and a use method and application thereof. The two-component conductive silver paste provided by the present invention has high shear strength and good conductivity after curing.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a two-component conductive silver paste, comprising independently packaged component A and component B:
[0006] Calculated by weight, the component A includes: 16.5-22.5 parts of epoxy resin A, 7.5-10.5 parts of epoxy resin B, 5-6 parts of epoxy diluent and 60-80 parts of silver powder; the epoxy resin A is a long-chain epoxy resin containing at least two benzene rings; the epoxy resin B is an aliphatic epoxy resin containing a diepoxy functional group;
[0007] Calculated by weight, the B component includes: 15-25 parts of aromatic amine curing agent, 20-30 parts of acid anhydride curing agent, 1-1.5 parts of functional additives and 45-60 parts of silver powder;
[0008] The mass ratio of the component A to the component B is 1:(1-2.5).
[0009] Preferably, the long-chain epoxy resin A includes one or two of bisphenol A epoxy resin, bisphenol F epoxy resin, resorcinol epoxy resin, biphenyl novolac epoxy resin and bisphenol A diglycidyl ester.
[0010] Preferably, the epoxy equivalent of the epoxy resin A is 165 to 200 g / eq.
[0011] Preferably, the aliphatic epoxy resin B includes one or two of 1,4-cyclohexanedimethanol diglycidyl ether, tetrahydro-o-dicarboxylic acid diglycidyl ester and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester.
[0012] Preferably, the epoxy equivalent of the epoxy resin B is 150 to 180 g / eq.
[0013] Preferably, the epoxy diluent includes one or more of butyl glycidyl ether, butanediol diglycidyl ether and neopentyl glycol diglycidyl ether.
[0014] Preferably, the aromatic amine curing agent includes m-phenylenediamine, diaminodiphenylmethane, m-phenylenediamine, diaminodiphenyl sulfone or a product obtained by the addition of an aromatic polyamine and monoglycidyl ether; the amine equivalent of the aromatic amine curing agent is 60 to 100 KOH / g.
[0015] Preferably, the anhydride curing agent includes cyclobutane-1,2-dicarboxylic anhydride or 1,2,3,5-cyclobutanetetracarboxylic anhydride; the anhydride equivalent of the anhydride curing agent is 20 to 32 g / mol.
[0016] The present invention also provides a method for using the two-component conductive silver paste described in the above technical solution, comprising: mixing component A and component B at room temperature and then curing them, wherein the curing temperature is 25-100°C.
[0017] The present invention also provides the application of the two-component conductive silver paste described in the above technical solution in precision electronic products.
[0018] The invention provides a two-component conductive silver paste, comprising independently packaged component A and component B: the component A comprises, by weight, 16.5-22.5 parts of epoxy resin A, 7.5-10.5 parts of epoxy resin B, 5-6 parts of epoxy diluent and 60-80 parts of silver powder; the epoxy resin A is a long-chain epoxy resin containing at least two benzene rings; the epoxy resin B is an aliphatic epoxy resin containing a diepoxy functional group; the component B comprises, by weight, 15-25 parts of an aromatic amine curing agent, 20-30 parts of an acid anhydride curing agent, 1-1.5 parts of a functional auxiliary agent and 45-60 parts of silver powder; the mass ratio of the component A to the component B is 1:(1-2.5). The invention is based on an epoxy resin A containing at least two benzene ring rigid structures, and can improve the shear strength of a two-component conductive silver paste; by adding an aliphatic epoxy resin B containing a diepoxy functional group, the diepoxy groups contained in the aliphatic epoxy resin are utilized to provide abundant crosslinking sites, and the saturated structure of the aliphatic epoxy resin provides sufficient curing shrinkage during the crosslinking process, and promotes the crosslinking reaction, thereby improving the conductivity of the two-component conductive silver paste; by using an aromatic amine curing agent and an acid anhydride curing agent to promote the curing of the epoxy resin A and the epoxy resin B, the shear strength and conductivity of the two-component conductive silver paste are improved; wherein the acid anhydride curing agent The curing process will affect the microstructure of the conductive adhesive, including the distribution, size and morphology of the conductive particles, which directly affects the conductivity of the conductive adhesive; and after the anhydride curing agent reacts with the epoxy resin, a network structure with a high cross-linking density will be formed, which helps to improve the mechanical strength and heat resistance of the conductive adhesive; during the curing process, the aromatic amine curing agent can form a stable cross-linking network structure with the resin matrix, which improves the mechanical properties and heat resistance of the cured product, and also helps to form a more uniform conductive network; in the conductive adhesive, the conductive particles are interconnected through these cross-linking points to form a continuous conductive channel, thereby improving the conductivity. The results of the embodiment show that the shear strength of the two-component conductive silver paste provided by the present invention can reach 13.96MPa, and the resistance can be as low as 21Ω. DETAILED DESCRIPTION
[0019] The present invention provides a two-component conductive silver paste, comprising independently packaged component A and component B:
[0020] Calculated by weight, the component A includes: 16.5-22.5 parts of epoxy resin A, 7.5-10.5 parts of epoxy resin B, 5-6 parts of epoxy diluent and 60-80 parts of silver powder; the epoxy resin A is a long-chain epoxy resin containing at least two benzene rings; the epoxy resin B is an aliphatic epoxy resin containing a diepoxy functional group;
[0021] Calculated by weight, the B component includes: 15-25 parts of aromatic amine curing agent, 20-30 parts of acid anhydride curing agent, 1-1.5 parts of functional additives and 45-60 parts of silver powder;
[0022] The mass ratio of the component A to the component B is 1:(1-2.5).
[0023] The two-component conductive silver paste provided by the invention comprises component A; the component A comprises, by weight, 16.5 to 22.5 parts of epoxy resin A, 7.5 to 10.5 parts of epoxy resin B, 5 to 6 parts of epoxy diluent and 60 to 80 parts of silver powder.
[0024] In the present invention, the component A includes 16.5 to 22.5 parts of epoxy resin A, preferably 17 to 20 parts by mass. In an embodiment of the present invention, the epoxy resin A may be specifically 16.5 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts or 22.5 parts.
[0025] In the present invention, the epoxy resin A is a long-chain epoxy resin containing at least two benzene rings. The present invention can improve the shear strength of the two-component conductive silver paste by adopting the epoxy resin A containing at least two benzene ring rigid structures. In the present invention, the epoxy resin A preferably includes one or two of bisphenol A type epoxy resin, bisphenol F type epoxy resin, resorcinol epoxy resin, biphenyl phenolic epoxy resin and bisphenol A type diglycidyl ester. The present invention can further improve the shear strength of the two-component conductive silver paste by limiting the type of epoxy resin A.
[0026] In the present invention, the epoxy equivalent of the epoxy resin A is preferably 165 to 200 g / eq. In an embodiment of the present invention, the epoxy equivalent of the epoxy resin A may be specifically 165 g / eq, 170 g / eq, 180 g / eq, 190 g / eq or 200 g / eq. The present invention more effectively adjusts the ratio of the resin in component A and the curing agent in component B by limiting the epoxy equivalent of the epoxy resin A, so that component A is cured more fully, thereby improving the tensile shear performance and conductivity of the two-component silver paste.
[0027] In the present invention, based on the mass fraction of epoxy resin A being 16.5 to 22.5 parts, the A component includes 7.5 to 10.5 parts of epoxy resin B, preferably 8 to 10 parts. In an embodiment of the present invention, the epoxy resin B may be specifically 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts or 10.5 parts. The present invention provides more abundant cross-linking sites by limiting the number of parts of epoxy resin B, and more fully cross-links with epoxy resin A, thereby obtaining a two-component silver paste with better conductive properties.
[0028] In the present invention, the epoxy resin B is an aliphatic epoxy resin containing a diepoxy functional group. The present invention improves the conductivity of the two-component conductive silver paste by adding an aliphatic epoxy resin B containing a diepoxy functional group, utilizing the diepoxy groups contained therein to provide abundant crosslinking sites, and the saturated structure of the aliphatic epoxy resin provides sufficient curing shrinkage during the crosslinking process. In the present invention, the aliphatic epoxy resin B preferably includes one or two of 1,4-cyclohexanedimethanol diglycidyl ether, tetrahydrophthalic acid diglycidyl ester and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester. The present invention further provides abundant crosslinking sites by limiting the type of aliphatic epoxy resin B, thereby further improving the conductivity of the two-component conductive silver paste.
[0029] In the present invention, the epoxy equivalent of the epoxy resin B is preferably 150 to 180 g / eq. In an embodiment of the present invention, the epoxy equivalent of the epoxy resin B may be specifically 150 g / eq, 160 g / eq, 170 g / eq or 180 g / eq. The present invention more effectively adjusts the ratio of the resin in component A and the curing agent in component B by limiting the epoxy equivalent of the epoxy resin B, so that component A is cured more fully, thereby improving the tensile shear performance and conductivity of the two-component silver paste.
[0030] In the present invention, based on 16.5 to 22.5 parts by mass of epoxy resin A, the A component includes 5 to 6 parts of epoxy diluent. In an embodiment of the present invention, the epoxy diluent may be specifically 5 parts, 5.5 parts or 6 parts. The present invention reduces the viscosity of the epoxy resin curing system by limiting the epoxy diluent, increases its fluidity, and prolongs its service life.
[0031] In the present invention, the epoxy diluent preferably includes one or more of butyl glycidyl ether, butanediol diglycidyl ether and neopentyl glycol diglycidyl ether. The present invention further effectively adjusts the viscosity of the epoxy resin curing system, increases its fluidity and prolongs its service life by limiting the type of epoxy diluent.
[0032] In the present invention, based on 16.5 to 22.5 parts by mass of epoxy resin A, the component A includes 60 to 80 parts of silver powder. In an embodiment of the present invention, the 60 to 80 parts of silver powder can be specifically 60 parts, 65 parts, 70 parts, 75 parts or 80 parts. The present invention improves the conductive properties of the two-component silver paste by limiting the amount of silver powder.
[0033] In the present invention, the silver powder preferably includes one or more of flaky silver powder, spherical silver powder and linear silver powder. The present invention reduces the volume resistivity of the two-component silver paste by limiting the shape of the silver powder, and further improves the conductive performance. In the present invention, the silver powder preferably includes micron-grade silver powder and submicron-grade silver powder. In the present invention, the particle size of the micron-grade silver powder is preferably 1 to 20 μm. In the embodiment of the present invention, the particle size of the micron-grade silver powder can be specifically 1 μm, 5 μm, 10 μm, 15 μm or 20 μm. In the present invention, the particle size of the submicron-grade silver powder is preferably 0.5 to 0.9 μm. In the embodiment of the present invention, the particle size of the submicron-grade silver powder can be specifically 0.5 μm, 0.8 μm, 0.7 μm, 0.8 μm or 0.9 μm. The present invention has a higher specific surface area by limiting the particle size of the silver powder, providing more conductive channels, thereby improving the conductive performance of the silver paste. In the present invention, the mass ratio of the micron-sized silver powder to the submicron-sized silver powder is preferably (1.5-4): 1. In an embodiment of the present invention, the mass ratio of the micron-sized silver powder to the submicron-sized silver powder may be specifically 1.5: 1, 2: 1, 3: 1 or 4: 1. The present invention further provides more conductive channels by limiting the mass ratio of the micron-sized silver powder to the submicron-sized silver powder, thereby improving the conductive performance of the silver paste.
[0034] In the present invention, the preparation method of the component A preferably comprises: mixing epoxy resin A, epoxy resin B, epoxy diluent and silver powder to obtain component A.
[0035] In the present invention, the mixing of the epoxy resin A, epoxy resin B, epoxy diluent and silver powder preferably comprises: firstly mixing the epoxy resin A, epoxy resin B and epoxy diluent, and then adding the silver powder and mixing.
[0036] In the present invention, the epoxy resin A, epoxy resin B and epoxy diluent are preferably mixed under stirring. In the present invention, the stirring time is preferably 2 minutes; and the stirring rate is preferably 1500-2000 rpm.
[0037] As an embodiment of the present invention, the mixture after adding silver powder is preferably rolled in a three-roll mill to obtain component A. In the present invention, the rolling interval is preferably 120 μm, 100 μm, 60 μm, 40 μm, 15 μm and 10 μm. In the present invention, the number of rolling at each interval is preferably 3 times.
[0038] In the present invention, the fineness of component A is preferably 10 μm. By limiting the fineness of component A, the present invention makes component A have better fluidity, dispersibility and permeability, and can be better mixed and cured with component B, thereby improving the tensile shear strength and conductivity of the two-component silver paste.
[0039] The two-component conductive silver paste provided by the present invention also includes a B component packaged separately from the A component; the B component includes, by mass, 15 to 25 parts of an aromatic amine curing agent, 20 to 30 parts of an acid anhydride curing agent, 1 to 1.5 parts of a functional auxiliary agent and 45 to 60 parts of silver powder.
[0040] In the present invention, the B component includes 15 to 25 parts of an aromatic amine curing agent by weight. In an embodiment of the present invention, the aromatic amine curing agent may be specifically 15 parts, 18 parts, 20 parts, 23 parts or 25 parts. The present invention promotes the curing of epoxy resin A and epoxy resin B by limiting the aromatic amine curing agent, thereby improving the shear strength of the two-component conductive silver paste.
[0041] In the present invention, the aromatic amine curing agent preferably includes m-phenylenediamine, diaminodiphenylmethane, m-phenylenediamine, diaminodiphenyl sulfone or a product obtained by the addition of an aromatic polyamine and monoglycidyl ether. The present invention further promotes the curing of epoxy resin A and epoxy resin B by limiting the type of aromatic amine curing agent, thereby improving the shear strength of the two-component conductive silver paste. At the same time, the aromatic amine curing agent can form a stable cross-linked network structure with the resin matrix during the curing process, thereby improving the mechanical properties and heat resistance of the cured product, and also helping to form a more uniform conductive network; in the conductive adhesive, the conductive particles are interconnected through these cross-linking points to form a continuous conductive channel, thereby improving the conductivity.
[0042] In the present invention, the amine equivalent of the aromatic amine curing agent is preferably 60 to 100 KOH / g. In an embodiment of the present invention, the amine equivalent of the aromatic amine curing agent may be specifically 60 KOH / g, 70 KOH / g, 80 KOH / g, 90 KOH / g or 100 KOH / g. The present invention more effectively adjusts the ratio of the resin in component A and the curing agent in component B by limiting the amine equivalent of the aromatic amine curing agent, so that component A is cured more fully, thereby improving the tensile shear performance and conductivity of the two-component silver paste.
[0043] In the present invention, the mass of the aromatic amine curing agent is 15 to 25 parts, and the B component includes 20 to 30 parts of anhydride curing agent. In an embodiment of the present invention, the anhydride curing agent may be specifically 20 parts, 22 parts, 25 parts, 28 parts or 30 parts. The present invention promotes the curing of epoxy resin A and epoxy resin B by limiting the anhydride curing agent, thereby improving the shear strength and conductivity of the two-component conductive silver paste; at the same time, after the anhydride curing agent reacts with the resin matrix, it can form a stable cross-linked network structure, which helps to reduce the pores and defects in the cured product, making the transmission path of electrons in the cured product smoother; at the same time, the reaction rate of the anhydride curing agent is relatively slow, the internal stress generated is small, and the shrinkage rate of the cured product is also small, which helps to maintain the stability and integrity of the conductive network. Therefore, the optimized cured product structure can improve the conductivity.
[0044] In the present invention, the anhydride curing agent preferably includes cyclobutane-1,2-dicarboxylic anhydride or 1,2,3,5-cyclobutanetetracarboxylic anhydride. The present invention further promotes the crosslinking of epoxy resin A and epoxy resin B into a network structure by limiting the type of anhydride curing agent, thereby improving the shear strength and conductivity of the two-component conductive silver paste.
[0045] In the present invention, the anhydride equivalent of the anhydride curing agent is preferably 20 to 32 g / mol. In an embodiment of the present invention, the anhydride equivalent of the anhydride curing agent may be specifically 20 g / mol, 25 g / mol, 28 g / mol, 30 g / mol or 32 g / mol. The present invention more effectively adjusts the ratio of the resin in component A and the curing agent in component B by limiting the anhydride equivalent of the anhydride curing agent, so that component A is cured more fully, thereby improving the tensile shear properties and conductivity of the two-component silver paste.
[0046] In the present invention, based on 15 to 25 parts by mass of the aromatic amine curing agent, the B component includes 1 to 1.5 parts of a functional additive. In an embodiment of the present invention, the functional additive may be specifically 1 part, 1.25 parts or 1.5 parts. The present invention effectively adjusts the performance of the two-component silver paste preparation process by limiting the functional additive, so that the obtained two-component silver paste has higher tensile shear strength and better conductivity.
[0047] In the present invention, the functional additive preferably includes one or more of a leveling agent, a thickener, a dispersant and a thixotropic agent. The present invention further improves the performance of the two-component silver paste in a targeted manner by limiting the types of functional additives, thereby obtaining a two-component silver paste with higher tensile shear strength and better conductivity.
[0048] In the present invention, based on 15 to 25 parts by weight of the aromatic amine curing agent, the B component includes 45 to 60 parts of silver powder. In an embodiment of the present invention, the silver powder may specifically be 45 parts, 55 parts or 60 parts.
[0049] In the present invention, the shape, particle size and mass ratio of micron-sized silver powder and submicron-sized silver powder of the silver powder are the same as those of the silver powder of component A, and are not described in detail here.
[0050] In the present invention, the preparation method of the B component preferably comprises: mixing an aromatic amine curing agent, an acid anhydride curing agent, a functional auxiliary agent and silver powder to obtain the B component.
[0051] In the present invention, the mixing of the aromatic amine curing agent, the acid anhydride curing agent, the functional auxiliary agent and the silver powder preferably comprises: firstly mixing the aromatic amine curing agent, the acid anhydride curing agent and the functional auxiliary agent, and then adding the silver powder and mixing.
[0052] In the present invention, the mixing of the aromatic amine curing agent, the acid anhydride curing agent and the functional auxiliary agent is preferably carried out under stirring. In the present invention, the stirring time is preferably 2 minutes; and the stirring rate is preferably 1500-2000 rpm.
[0053] As an embodiment of the present invention, the mixture after adding silver powder is preferably rolled in a three-roll mill to obtain component B. In the present invention, the rolling interval is preferably 120 μm, 100 μm, 60 μm, 40 μm, 15 μm and 10 μm. In the present invention, the number of rolling at each interval is preferably 3 times.
[0054] In the present invention, the fineness of component B is preferably 8 μm. By limiting the particle size of component B, the present invention makes component B have better fluidity, dispersibility and permeability, and can be better mixed and cured with component A, thereby improving the tensile shear strength and conductivity of the two-component silver paste.
[0055] In the present invention, the mass ratio of component A to component B is 1: (1-2.5), preferably 1: 2. The present invention limits the mass ratio of component A to component B to make the prepared two-component silver paste have higher shear strength and better conductivity.
[0056] The invention is based on an epoxy resin A containing at least two benzene ring rigid structures, and can improve the shear strength of a two-component conductive silver paste; by adding an aliphatic epoxy resin B containing a diepoxy functional group, the diepoxy groups contained in the aliphatic epoxy resin are utilized to provide abundant crosslinking sites, and the saturated structure of the aliphatic epoxy resin provides sufficient curing shrinkage during the crosslinking process, thereby improving the conductivity of the two-component conductive silver paste; by using an aromatic amine curing agent and an acid anhydride curing agent to promote the epoxy resin A and the epoxy resin B to be crosslinked into a network structure, the shear strength and conductivity of the two-component conductive silver paste are improved.
[0057] The present invention also provides a method for using the two-component conductive silver paste described in the above technical solution, comprising: mixing component A and component B at room temperature and then curing them.
[0058] The present invention has no special limitation on the mixing of the component A and the component B at room temperature, and any mixing method known in the art may be used.
[0059] In the present invention, the curing temperature is preferably 80° C. When the curing temperature is 25° C., the curing time is preferably 24 hours; when the curing temperature is 80° C., the curing time is preferably 1 hour.
[0060] The two-component conductive silver paste obtained by mixing and curing component A and component B at room temperature has high shear strength and good conductivity.
[0061] The present invention also provides the application of the two-component conductive silver paste described in the above technical solution in precision electronic products.
[0062] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] Example 1
[0064] A two-component conductive silver paste, consisting of independently packaged component A and component B:
[0065] The composition of component A is as follows, by mass: 13.5 parts of chain epoxy resin DER321, 39 parts of chain epoxy resin DER38, 27.5 parts of alicyclic epoxy resin S-18, 5 parts of epoxy diluent butanediol diglycidyl ether, 30 parts of 5 μm micron-sized flaky silver powder, and 35 parts of 10 μm micron-sized flaky silver powder;
[0066] The composition of the B component is as follows: 120 parts of aromatic amine curing agent T3, 25 parts of cyclobutane-1,2-dicarboxylic anhydride, 1 part of functional auxiliary thixotropic agent BYK-410 and 54 parts of silver powder, calculated by mass.
[0067] The mass ratio of component A to component B is 1.2:1;
[0068] The preparation method of the above-mentioned component A is to stir epoxy resin A, epoxy resin B and epoxy diluent at 2000rpm for 2min, then add silver powder and mix, and then place the mixed solution in a three-roll mill for rolling to obtain component A with a particle size of less than 10μm; the rolling intervals are 120μm, 100μm, 60μm, 40μm, 15μm and 10μm; the number of rolling times for each interval is 3 times.
[0069] Example 2
[0070] The difference between this embodiment and embodiment 1 is that: component A includes 121 parts of chain epoxy resin DER32 and 29 parts of alicyclic epoxy resin S-18; the rest is the same as embodiment 1.
[0071] Example 3
[0072] The difference between this embodiment and embodiment 1 is that: component A includes 6.5 parts of chain epoxy resin DER3211, 8.5 parts of alicyclic epoxy resin S-182, 35 parts of 5 μm micron-sized flaky silver powder, and 35 parts of 10 μm micron-sized flaky silver powder; the rest is the same as embodiment 1.
[0073] Example 4
[0074] The difference between this embodiment and embodiment 1 is that: component A includes 120 parts of chain epoxy resin DER32, 29 parts of alicyclic epoxy resin S-18, and 6 parts of epoxy diluent; the rest is the same as embodiment 1.
[0075] Example 5
[0076] The difference between this embodiment and embodiment 1 is that: component B includes 18 parts of aromatic amine curing agent T3 and 27 parts of cyclobutane-1,2-dicarboxylic anhydride; the rest is the same as embodiment 1.
[0077] Comparative Example 1
[0078] The difference between this comparative example and Example 1 is that: Component A includes 210 parts of chain epoxy resin DER3 and 230 parts of alicyclic epoxy resin S-18; the rest is the same as Example 1.
[0079] Comparative Example 2
[0080] The difference between this comparative example and Example 1 is that: Component A includes 130 parts of chain epoxy resin DER32 and 20 parts of alicyclic epoxy resin S-18; the rest is the same as Example 1.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 1 is that: Component B includes 10 parts of aromatic amine curing agent T3 and 45 parts of cyclobutane-1,2-dicarboxylic anhydride; the rest is the same as Example 1.
[0083] Comparative Example 4
[0084] The difference between this comparative example and Example 1 is that: Component A: 17.5 parts of chain epoxy resin DER321, 70 parts of silver powder; Component B: 45 parts of aromatic amine curing agent T31, 0 parts of cyclobutane-1,2-dicarboxylic anhydride; the rest is the same as Example 1.
[0085] The performance tests were performed on the two-component conductive silver pastes of Examples 1 to 5 and Comparative Examples 1 to 4:
[0086] (1) Tensile shear strength test: Test according to the test method provided in the national standard "GB / T 7124-2006 Determination of tensile shear strength of adhesives (rigid material to rigid material)";
[0087] After mixing and stirring components A and B at room temperature for 2 minutes, they were coated on 2mm thick cold-rolled steel strip CRS1403, with a bonding area of 25×12.5mm, and cured at room temperature for 24 hours; then, the same components A and B were mixed and stirred at room temperature for 2 minutes, coated on 2mm thick cold-rolled steel strip CRS1403, with a bonding area of 25×12.5mm, and cured at 80°C for 1 hour. The two groups of cured steel strips were tested at room temperature using a universal material testing machine at a test rate of 5mm / min, and the tensile shear strength at room temperature was obtained, as shown in Table 1.
[0088] (2) Conductivity test:
[0089] Use tape to stick three 9×1cm rectangular frames on the float glass, mix and stir component A and component B at room temperature for 2 minutes, apply them on the rectangular frames of the float glass, and cure them at room temperature for 24 hours; then mix and stir the same component A and component B at room temperature for 2 minutes, apply them on the rectangular frames of the float glass with the same operation, and cure them at 80℃ for 1 hour. Use a multimeter to measure the resistance of the two groups of float glass after curing, as shown in Table 1.
[0090] Table 1 Performance data of the two-component conductive silver paste prepared in Examples 1 to 5 and Comparative Examples 1 to 4
[0091]
[0092] It can be seen from Table 1 that the tensile shear strength and conductivity of the two-component conductive silver paste of the present invention are similar when cured at room temperature and cured at 80°C for 1 hour, indicating that the two-component conductive silver paste of the present invention has high tensile shear strength and good conductivity after being cured at room temperature.
[0093] By comparing the two-component conductive silver paste obtained in Example 1 of the present invention with Comparative Example 1, it can be found that the two-component conductive silver paste obtained by omitting the addition of epoxy resin A has a reduced tensile shear strength, indicating that epoxy resin A can enhance the tensile shear strength of the two-component conductive silver paste.
[0094] By comparing the two-component conductive silver paste obtained in Example 1 of the present invention with Comparative Example 2, it can be found that the conductivity of the two-component conductive silver paste obtained by omitting the addition of epoxy resin B is reduced, indicating that epoxy resin B can enhance the conductivity of the two-component conductive silver paste.
[0095] By comparing the two-component conductive silver paste obtained in Example 1 of the present invention with Comparative Example 3, it can be found that the conductivity of the two-component conductive silver paste obtained by omitting the addition of the aromatic curing agent is reduced, indicating that the aromatic curing agent can enhance the conductivity of the two-component conductive silver paste.
[0096] By comparing the two-component conductive silver paste obtained in Example 1 of the present invention with Comparative Example 5, it can be found that the two-component conductive silver paste obtained by omitting the addition of cyclobutane-1,2-dicarboxylic anhydride (anhydride curing agent) has reduced tensile shear strength and conductivity, indicating that adding anhydride curing agents can improve the tensile shear strength and conductivity of the two-component conductive silver paste.
[0097] In summary, the two-component conductive silver paste provided by the present invention has high shear strength and good conductivity after being cured at room temperature.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A two-component conductive silver paste, comprising independently packaged component A and component B: Calculated by mass, the A component includes: 16.5-22.5 parts of epoxy resin A, 7.5-10.5 parts of epoxy resin B, 5-6 parts of epoxy diluent and 60-80 parts of silver powder; the epoxy resin A is a long-chain epoxy resin containing at least two benzene rings; The epoxy resin B is an aliphatic epoxy resin containing a diepoxy functional group; Calculated by weight, the B component includes: 15-25 parts of aromatic amine curing agent, 20-30 parts of acid anhydride curing agent, 1-1.5 parts of functional additives and 45-60 parts of silver powder; The mass ratio of the component A to the component B is 1:(1-2.5).
2. The two-component conductive silver paste according to claim 1, characterized in that: The epoxy resin A includes one or two of bisphenol A epoxy resin, bisphenol F epoxy resin, resorcinol epoxy resin, biphenyl novolac epoxy resin and bisphenol A diglycidyl ester.
3. The two-component conductive silver paste according to claim 1 or 2, characterized in that: The epoxy equivalent of the epoxy resin A is 165 to 200 g / eq.
4. The two-component conductive silver paste according to claim 1, characterized in that: The aliphatic epoxy resin B includes one or two of 1,4-cyclohexanedimethanol diglycidyl ether, tetrahydro-o-dicarboxylic acid diglycidyl ester and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester.
5. The two-component conductive silver paste according to claim 1 or 4, characterized in that: The epoxy equivalent of the epoxy resin B is 150 to 180 g / eq.
6. The two-component conductive silver paste according to claim 1, characterized in that: The epoxy diluent includes one or more of butyl glycidyl ether, butanediol diglycidyl ether and neopentyl glycol diglycidyl ether.
7. The two-component conductive silver paste according to claim 1, characterized in that: The aromatic amine curing agent includes metaphenylenediamine, diaminodiphenylmethane, metaphenylenediamine, diaminodiphenyl sulfone or a product obtained by adding aromatic polyamine to monoglycidyl ether; the amine equivalent of the aromatic amine curing agent is 60-100KOH / g.
8. The two-component conductive silver paste according to claim 1, characterized in that: The acid anhydride curing agent includes cyclobutane-1,2-dicarboxylic anhydride or 1,2,3,5-cyclobutanetetracarboxylic anhydride; the anhydride equivalent of the acid anhydride curing agent is 20 to 32 g / mol.
9. The method for using the two-component conductive silver paste according to any one of claims 1 to 8, comprising: The A component and the B component are mixed at room temperature and then cured. The curing temperature is 25-100°C.
10. Use of the two-component conductive silver paste according to any one of claims 1 to 8 in precision electronic products.